2002
DOI: 10.2169/internalmedicine.41.1142
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Pancreatitis Successfully Treated with Ursodeoxycholic Acid.

Abstract: A 51-year-old womanwith autoimmune pancreatitis is reported in whomtreatment with ursodeoxycholic acid (UDCA) was beneficial. Complaining of epigastric discomfort, she presented with liver dysfunction of the cholestatic type, and diabetes mellitus. Pancreatic imaging revealed a diffuse swelling of the body, an irregular narrowing of the main pancreatic duct, and a terminal stricture of the common bile duct. Histologically, the biopsied pancreas was replaced by fibrous tissue with a small amount of mononuclear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 9 publications
0
9
0
3
Order By: Relevance
“…Therefore, pharmacological agents that promote eIF-2␣ phosphorylation and ATF4 induction without adding to cell stress may be useful tools in a wide range of clinical situations in anticipation of cellular injury. It may further explain successful treatments of idiopathic and autoimmune pancreatitis by bile salts demonstrated in several case reports and small pilot studies in humans (49,57,59). Thus this treatment strategy may become important, even since a recent publication showed a connection between ER stress and chronic hereditary pancreatitis (26).…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, pharmacological agents that promote eIF-2␣ phosphorylation and ATF4 induction without adding to cell stress may be useful tools in a wide range of clinical situations in anticipation of cellular injury. It may further explain successful treatments of idiopathic and autoimmune pancreatitis by bile salts demonstrated in several case reports and small pilot studies in humans (49,57,59). Thus this treatment strategy may become important, even since a recent publication showed a connection between ER stress and chronic hereditary pancreatitis (26).…”
Section: Discussionmentioning
confidence: 91%
“…In connection with future in vivo studies, the data may open new perspectives on the use of chemical chaperones as a therapeutic approach optimizing exocrine pancreas function and reducing pancreatic cell damage under conditions of overstimulation and inflammation. It may further explain successful treatments of idiopathic and autoimmune pancreatitis by bile salts demonstrated in several case reports and small pilot studies in humans (38,46,49). Thus this treatment strategy may become important, even though a recent publication showed a connection between ER stress and hereditary pancreatitis (19).…”
Section: G883mentioning
confidence: 93%
“…19 In one case of AIP, it was reported that UDCA was effective for diabetes mellitus and pancreatic swelling, as well as the liver dysfunction. 20 UDCA is well known to be effective for primary biliary cirrhosis (PBC) through its bile fl ow increment and immune-modulation activity. UDCA may be an alternative therapy for AIP, especially in cases involving the biliary tract, but further studies to clarify the pathogenesis and establish a standard therapy are necessary.…”
Section: Methods Of Treatment For Patients With Aip From An Epidemiolmentioning
confidence: 99%